A novel loop-mediated isothermal amplification-based test for detecting Neospora caninum DNA (2017)
Background: Neospora caninum is a cyst-forming, coccidian parasite which is known to cause neurological disorders in dogs and abortion and neonatal mortality in cows and other livestock. This study reports the development of a loop-mediated isothermal amplification (LAMP) assay based on the Neospora caninum Nc-5 gene and compares its efficacy for detecting DNA to that of a semi-nested PCR test. Results: Six primers were designed based on the Nc-5 repeat region of N. caninum. Specific LAMP primers led to successful amplification of N. caninum DNA at 63 °C in 30 min. The LAMP assay was highly specific (i.e. it did not reveal cross-reactivity with other parasite species) and had a low N. caninum plasmid DNA limit of detection (1 fg), which is ten times higher than that for the semi-nested PCR. LAMP applicability was evaluated using a set of naturally-infected samples (59 from canine faeces and five from bovine abortions). Thirty-nine percent (25/64) of the naturally-infected samples were positive for N. caninum DNA by LAMP and 36% (23/64) by semi-nested PCR. However, the LAMP assay is much faster to perform than semi-nested PCR and provides results in 30 min. Conclusion: The optimized reaction conditions described in this study resulted in a sensitive, specific and rapid technique for detecting N. caninum DNA. Considering the advantages of LAMP for detecting N. caninum DNA, further assays aimed at testing its usefulness on a wider range of field samples are recommended. © 2017 The Author(s).